Antibiotic resistance in medical practice: causes and ways to overcome it in Ukraine (Perioperaciina Medicina, 2024)
In todays world, the use of antibiotics is not limited to the medical field; they are also actively used in many areas of our life, including agriculture. The widespread and uncontrolled use of antibiotics leads to the growth of antibiotic resistance, which results in the emergence of new resistant strains of microorganisms every day, complicating the course of many infectious diseases. This publication highlights current views on the main causes, mechanisms of microbial resistance, and measures taken in Ukraine to overcome it by implementing the main modern European guidelines and orders of the Ministry of Health of Ukraine.
Keywords: antimicrobial resistance; causes of AMR; mechanism of AMR development; ways to overcome it